Epilepsy - Advances in Diagnosis and Therapy 2019
DOI: 10.5772/intechopen.83698
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels in Epilepsy: Blasting Fuse for Neuronal Hyperexcitability

Abstract: Voltage-gated ion channels (VGICs), extensively distributed in the central nervous system (CNS), are responsible for the generation as well as modulation of neuroexcitability and considered as vital players in the pathogenesis of human epilepsy, with regulating the shape and duration of action potentials (APs). For instance, genetic alterations or abnormal expression of voltage-gated sodium channels (VGSCs), Kv channels, and voltage-gated calcium channels (VGCCs) are proved to be associated with epileptogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 116 publications
0
10
0
1
Order By: Relevance
“…Ion channel dysfunction, either caused by mutations or acquired, has been associated with epilepsy. Many AEDs tend to manipulate the ion permeability of these channels to modify neuronal excitability [ 78 ]. In the present study, we have demonstrated the up-regulation of AQP1, KCNK10, KCNH8, P2RX7, SGK1, SGK2, SLC12A2, SLC6A2, SLC44A1, SLC45A3, SCLC5A11, SCL26A9, CLCA4 and SEPT4 in MAX of FCD type II patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion channel dysfunction, either caused by mutations or acquired, has been associated with epilepsy. Many AEDs tend to manipulate the ion permeability of these channels to modify neuronal excitability [ 78 ]. In the present study, we have demonstrated the up-regulation of AQP1, KCNK10, KCNH8, P2RX7, SGK1, SGK2, SLC12A2, SLC6A2, SLC44A1, SLC45A3, SCLC5A11, SCL26A9, CLCA4 and SEPT4 in MAX of FCD type II patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of SLC12A2 has been reported in surgically resected tissue specimens from FCD patients [ 85 ]. SLC26A9 , a highly selective chloride ion channel, CLCA4 , calcium sensitive chloride channel, SLC45A3 , SLC5A11 may be involved in ion transport and neurotransmitter release in FCD [ 78 ]. SLC44A1, a choline transporter, may contribute to membrane synthesis and myelin production.…”
Section: Discussionmentioning
confidence: 99%
“…Voltage gated sodium channels (VGSC) are often a therapeutic target for epilepsies (Mantegazza et al 2010). The Nav1.1 is present primarily in inhibitory gabaergic neurons (Zhang et al 2019). Mutations causing loss of function of Nav 1.1 can induce severe untreatable epilepsies (Mantegazza et al 2005).…”
Section: Lack Of Effects Of Canatoxin On Voltage Gated Ion Channels A...mentioning
confidence: 99%
“…Mutations causing loss of function of Nav 1.1 can induce severe untreatable epilepsies (Mantegazza et al 2005). If Nav1.1 currents are blocked, the inhibition in a given neural network is reduced because of impaired gabaergic signaling, so that excitatory neurons would fire excessively causing seizures (Zhang et al 2019). It has been demonstrated a striking relationship between the neuronal Nav 1.6 and spike wave discharges, the hallmark of epilepsy crises (Papale et al 2009).…”
Section: Lack Of Effects Of Canatoxin On Voltage Gated Ion Channels A...mentioning
confidence: 99%
“…In addition, also deletions and duplications of (part of) the gene can strongly affect normal channel function (Borlot et al, 2017;Monlong et al, 2018). Since the focus of this review is on the transcriptional regulation of ion channels, listing all genetic variants within the coding regions of ion channel genes is beyond the scope of this article (for reviews, see Deng et al, 2014;Wei et al, 2017;Zhang et al, 2019).…”
Section: Voltage-gated and Ligand-gated Ion Channels In Genetic Epilementioning
confidence: 99%